KONTRIBUSI JENIS USAHATANI SAYURAN TERHADAP PENDAPATAN POLA USAHATANI DI KOTA MATARAM - Aeko Fria Utama FR; Fadli Fadli (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2023)
The aims of the study were to determine the dominant types of vegetables cultivated in the city of Mataram, to determine the contribution of each vegetable to the total income of farming patterns in the city of Mataram, to analyze the efficiency of vegetable farming in the city of Mataram. This research uses a descriptive method. Data collection techniques use survey techniques. Types of quantitative and qualitative data, data sources are primary data and secondary data. This research was conducted in Pejarakan Karya Village, Ampenan District. Of the 4 neighborhoods in the Pejarakan Karya Village, the Moncok Karya neighborhood was determined as a sample by purposive sampling on the basis of the largest number of vegetable farmers. The number of respondents was determined by quota sampling, namely as many as 30 respondents selected by random sampling. The analysis used is the analysis of income and contributions. The results showed that there were six types of dominant lowland vegetable plants that were cultivated, namely: spinach vegetables, lettuce vegetables, flower vegetables, pakcoy vegetables, caisim vegetables, and sweet vegetables. The average contribution of plant income for each type of lowland vegetable plant to total agricultural pattern income is 29.64% pakcoy vegetables, 27.49% lettuce vegetables, 25.88% caisim vegetables, 7.40% sweet vegetables, 5.39 % flower vegetables, and 6.73% spinach vegetables, of the six dominant types of vegetable plants that are most efficient for cultivation, namely pakcoy vegetables with an R/C ratio of 3.82.